Refractive Accuracy of Barrett True-K vs Intraoperative Aberrometry for IOL Power Calculation in Post-Corneal Refractive Surgery Eyes - Gouvea L (Dove Medical Press, 2021)
Larissa Gouvea,1,2 Kareem Sioufi,3 Colin E Brown,3 George Waring IV,4 Wallace Chamon,2 Karolinne Maia Rocha3 1Department of Ophthalmology and Visual Sciences, University of Toronto, Toronto, ON, Canada; 2Department of Ophthalmology and Visual Sciences, Federal University of São Paulo, São Paulo, Brazil; 3Storm Eye Institute, Medical University of South Carolina, Charleston, SC, USA; 4Waring Vision Institute, Mount Pleasant, SC, USACorrespondence: Larissa Gouvea Toronto Western Hospital - 399 Bathurst Street, 6th Floor East Wing, Reception 1, Toronto, ON, M5T 2S8, CanadaTel +1 416 603-5401Fax +1 416 603-1993Email gouveaalarissa@gmail.comPurpose: To compare the refractive predictability of intraoperative aberrometry (IA, ORA, Alcon) and Barrett True-K/Universal II formulas for intraocular lens (IOL) power calculations in post-corneal refractive surgery and normal eyes.Methods: Retrospective study of normal and post-corneal refractive surgery eyes that underwent cataract surgery with IA at tertiary academic center. Preoperatively, IOL power calculations were performed using Barrett Universal II (normal eyes) or Barrett True-K (post-corneal refractive surgery eyes) formulas. Intraoperatively, aphakic IA measurements were used for IOL power calculations. Mean absolute refractive prediction error (MAE) and the percentage of eyes with prediction error within ± 0.50, ± 0.75 and ± 1.00 D were calculated. Refractive predictability was also evaluated in short, normal, and long eyes.Results: Two hundred and seventy-three eyes were included in the analysis. No statistically significant differences were observed between the MAE of preoperative formulas and IA for post-hyperopic laser vision correction (LVC), post-myopic LVC, post-radial keratotomy (RK) and normal eyes. For prediction error within ± 0.5 D in post-corneal refractive surgery eyes, range of agreement between Barrett True-K and IA ranged from 28% (7/25) of the time in post-RK eyes to 49% (40/81) of the time in post-hyperopic LVC; the corresponding value for Barrett Universal II/IA was 62% (64/103) in normal eyes. When there was disagreement, IA outperformed Barrett True-K in post-hyperopic LVC eyes and Barrett formula outperformed IA in post-myopic LVC, post-RK, and normal eyes.Conclusion: IA appears to be comparable to Barrett formulas for IOL power calculations in post-corneal refractive surgery and normal eyes. In post-hyperopic LVC, IA yields better results compared to Barrett True-K formula; in real-life scenarios, IA reveals statistical advantage over the Barrett True-K no history formula for eyes post-hyperopic LVC.Keywords: intraoperative aberrometry, eyes post refractive surgery, refractive outcomes, Barrett True-K formula